OVERHEAD COSTS AND INCOME MEASUREMENT. - Ferrara, William L. (The Accounting Review, 1961)
Abstract Income can be measured properly only when every attempt is made to segregate and allocate overhead costs to units of output so that costs of products may be matched or associated with the revenues derived from the sale of merchandise. To accomplish this task the generally accepted fixed-variable cost breakdown should be discarded for income measurement purposes. The straight-line amortization of costs associated with fixed assets should also be discarded. In place of straight-line amortization, a unit-of-output amortization plan or an approximation thereto should be used. The approximation would be the cycle overhead concept. The fixed cost portion of semi-variable cost inputs should be reassociated with their variable counterparts and then allocated to the output for which they were absolutely necessary elements of production. Finally, unit costs should be allowed to fluctuate with volume within the range for which semi-variable cost inputs are absolutely necessary costs of production.